Brokers of faith, brokers of empire : Armenians and the politics of reform in the Ottoman Empire - Antaramian, Richard E. (Stanford University Press, 2020)
"This book argues against the dominant historical view that Ottoman Armenians were united in resisting empire. Drawing on underused Armenian sources and archives, Richard Antaramian reveals the critical role the Armenian Church and clergy played in the implementation of the Ottoman state's reform efforts during the mid-nineteenth century Tanzimat era. Antaramian rethinks conceptions of the Ottoman state in terms of center and periphery, offering a networked model of empire in its place. This orients us to a view of a more dynamic political space, which has implications for understanding the Ottoman Empire, nationalism in the Middle East, and empires in general"--